2021
DOI: 10.1111/pace.14413
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for atrial fibrillation in elderly patients: Systematic review and a meta‐analysis

Abstract: Aims: Catheter ablation (CA) is established therapy for patients with atrial fibrillation (AF); however, there is a limited understanding of CA in elderly patients. We studied the long-term efficacy and periprocedural safety of radiofrequency and cryoballoon CA for elderly patients with AF.Methods: PubMed and Embase were searched through April 2021 to investigate the comparative outcomes between elderly and non-elderly patients who underwent CA for AF. The primary efficacy and safety endpoints were AF recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
7
2
Order By: Relevance
“…Moreover, we comprehensively investigated the explanations for primary outcomes, such as use of antiarrhymic agents, impacts of comorbidities, and broader individual complications. Notably, we did not find any significant differences in stroke risks contrasting to the other report 40 . We surmised that the influence of single predominating study , 41 wider‐defined age groups and smaller inherent studies might render the conflicting finding in the previous report .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, we comprehensively investigated the explanations for primary outcomes, such as use of antiarrhymic agents, impacts of comorbidities, and broader individual complications. Notably, we did not find any significant differences in stroke risks contrasting to the other report 40 . We surmised that the influence of single predominating study , 41 wider‐defined age groups and smaller inherent studies might render the conflicting finding in the previous report .…”
Section: Discussioncontrasting
confidence: 99%
“…While similar conclusion was drawn for AA recurrences, our result disagreed the latter from the previous study. It was highly likely that the previous study was affected by insufficient elderly participants > 75 years old, alluding to an underpower analysis . Subsequently, another meta‐analysis was performed by Kawamura et al , 40 finding no difference in AA recurrence but higher complications rates in elderly patients, in line with our study findings. Despite this similarity, several distinctions should be made aware.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this regard, the key to delivering a higher clinical benefit and avoiding pointless procedures in very ill patients may lie in superior patient selection. Some meta-analyses concluded that elderly patients’ long-term catheter ablation for AF effectiveness was equivalent to that of non-elderly patients’, but the incidence of operational complications was higher in elderly patients [ 39 , 40 ]. These findings imply that increased caution and concern for complications should be used when performing invasive cardiac procedures on elderly patients.…”
Section: Discussionmentioning
confidence: 99%